25th AIAA/CEAS Aeroacoustics Conference 2019
DOI: 10.2514/6.2019-2741
|View full text |Cite
|
Sign up to set email alerts
|

Airfoil-Turbulence Interaction Noise Source Identification and its Reduction by Means of Leading Edge Serrations

Abstract: The present work is aimed at assessing leading-edge serrations as an airfoil turbulenceimpingement noise (TIN) reduction mean. It relies on extended anechoic wind-tunnel testing including far-field measurements over an observation sphere to infer the three-dimensional features of TIN, and on microphone-array measurements to extract leading-edge noise in frequency. In particular this allows measuring unambiguously reductions of up to 15 dB achieved by serrations on flat plates. A preliminary study of the three-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 20 publications
(34 reference statements)
1
31
0
Order By: Relevance
“…The tip plane of the rear serrated airfoil exhibits a fundamentally different behavior possibly due to the emergence of counter-rotating vortices from the tip (tip flow), as previously observed through PIV Q5 measurements. 40,41 The serration tip plane measures the impact of Phys. Fluids 32, 000000 (2020); doi: 10.1063/5.0012958 32, 000000-9…”
Section: Unsteady Surface Pressurementioning
confidence: 99%
“…The tip plane of the rear serrated airfoil exhibits a fundamentally different behavior possibly due to the emergence of counter-rotating vortices from the tip (tip flow), as previously observed through PIV Q5 measurements. 40,41 The serration tip plane measures the impact of Phys. Fluids 32, 000000 (2020); doi: 10.1063/5.0012958 32, 000000-9…”
Section: Unsteady Surface Pressurementioning
confidence: 99%
“…In recent years there has been considerable interest in the use of leading edge (LE) serrations aimed at reducing interaction noise [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, most of these papers were focused on single-wavelength serrated leading edge profiles.…”
Section: A Single-wavelengthmentioning
confidence: 99%
“…While conducting acoustic tunnel measurements, Amiet [8] observed that the grid-generated turbulence approached the condition of isotropic turbulence in the test section of the tunnel, with a good agreement with von Kármán spectrum model. This near isotropic condition was, however, achieved in the absence of the airfoil in the test chamber of the acoustic tunnel, and it has been replicated in several studies such as in Devenport et al [10], Bampanis et al [11] and Juknevicius and Chong [12].…”
Section: Introductionmentioning
confidence: 61%